2020
DOI: 10.1136/neurintsurg-2020-015971
|View full text |Cite
|
Sign up to set email alerts
|

Rebleeding and bleeding in the year following intracranial aneurysm coiling: analysis of a large prospective multicenter cohort of 1140 patients—Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) Study

Abstract: BackgroundEndovascular treatment is the first line therapy for the management of ruptured and unruptured intracranial aneurysms, but delayed aneurysm rupture leading to bleeding/rebleeding can occur subsequently. ARETA (Analysis of Recanalization after Endovascular Treatment of intracranial Aneurysm) is a prospective, multicenter study conducted to analyze aneurysm recanalization. We analyzed delayed bleeding and rebleeding in this large cohort.Methods16 neurointerventional departments prospectively enrolled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The analysis results showed that the cause of subarachnoid hemorrhage was aneurysm rupture in about 8 cases per 100,000 people every year. With the enlargement of the arterial tumor, the probability of aneurysm rupture will increase exponentially, so the active treatment of intracranial aneurysm is particularly important [ 3 ]. However, some aneurysms, such as large or giant aneurysms, wide-necked aneurysms, fusiform aneurysms, and other complex aneurysms, have always been a difficult and challenging problem in clinical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis results showed that the cause of subarachnoid hemorrhage was aneurysm rupture in about 8 cases per 100,000 people every year. With the enlargement of the arterial tumor, the probability of aneurysm rupture will increase exponentially, so the active treatment of intracranial aneurysm is particularly important [ 3 ]. However, some aneurysms, such as large or giant aneurysms, wide-necked aneurysms, fusiform aneurysms, and other complex aneurysms, have always been a difficult and challenging problem in clinical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated a very low incidence of rebleeding for ruptured aneurysms and bleeding for unruptured aneurysms after coil embolization 48 , 49) along with risk factors for the aneurysm rupture. 48) Although the correlation between bleeding from coiled aneurysms and recanalization has not been well clarified, we believe that aggressive intervention for recanalized aneurysms is one of the reasons for this low rupture rate of coil aneurysms. Therefore, watchful imaging follow-up is still important and the craniogram will be a promising modality for coiled aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…According to ARETA study, the risk of rebleeding 1 year after coiling was estimated at 1.0%. Aneurysm occlusion and dome-to-neck ratio were the two factors that had appeared to play a role in the rebleeding [28].…”
Section: Discussionmentioning
confidence: 99%